Characterizing cometary electrons with kappa distributions. Issue 8 (12th August 2016) - Broiles, T. W.; Livadiotis, G.; Burch, J. L.; Chae, K.; Clark, G.; Cravens, T. E.; Davidson, R.; Eriksson, A.; Frahm, R. A.; Fuselier, S. A.; Goldstein, J.; Goldstein, R.; et al.
Abstract: The Rosetta spacecraft has escorted comet 67P/Churyumov‐Gerasimenko since 6 August 2014 and has offered an unprecedented opportunity to study plasma physics in the coma. We have used this opportunity to make the first characterization of cometary electrons with kappa distributions. Two three‐dimensional kappa functions were fit to the observations, which we interpret as two populations of dense and warm (density = 10 cm −3, temperature = 2 × 10 5 K, invariant kappa index = 10−>1000), and rarefied and hot (density = 0.005 cm −3, temperature = 5 × 10 5 K, invariant kappa index = 1–10) electrons. We fit the observations on 30 October 2014 when Rosetta was 20 km from 67P, and 3 AU from the Sun. We repeated the analysis on 15 August 2015 when Rosetta was 300 km from the comet and 1.3 AU from the Sun. Comparing the measurements on both days gives the first comparison of the cometary electron environment between a nearly inactive comet far from the Sun and an active comet near perihelion. We find that the warm population density increased by a factor of 3, while the temperature cooled by a factor of 2, and the invariant kappa index was unaffected. We find that the hot population density increased by a factor of 10, while the temperature and invariant kappa index were unchanged. We conclude that the hot population is likely the solar wind halo electrons in the coma. The warm population is likely of cometary origin, but its mechanism for production is not known. Key Points: The IES observed cometary electron environment is well characterized with 2 kappa distributions The hot electron population is likely the solar wind halo electrons The warm electron population is a poorly understood minority, possibly of cometary origin